Reduction of mispriming in amplification reactions with restricted PCR. - Puskás, L G; Bottka, S (Genome Research, 1995)
A simple method is described for reducing nonspecific background, which is caused by mispriming during PCR. Besides the standard pair of primers, 3'-dideoxy-terminated competitor oligonucleotides were added to the amplification. Sequences to those of the primers which had identical base. In this way enhanced specificity was achieved. The competitor oligonucleotides may act by masking possible sites of nonspecific primer-template interaction, thus excluding undesired chain extensions. This technique is generally applicable when highly degenerate primers are used and therefore expands the potential of "restricted" PCR.
10.1101/gr.5.3.309